Mineralization of Dentinal Lesions with Different Concentrations of Fluoride - Ayah A. Al-Asmar (Hindawi Limited, 2024)
Objectives. The present study aimed to investigate the relationship between fluoride concentration and mineral distribution within the dentinal lesion body. Methods. Remineralization of artificial deep dentinal lesions with various levels of fluoride was studied using a scanning electron microscope, microhardness tests, and polarized light microscope. Human molars were exposed to demineralization at pH 5.0 for 2 weeks. Then, they were divided into different groups for remineralization with different fluoride concentrations (0.1-10.0 ppm) for 1, 2, 3, and 4 weeks. Results. The results indicated a proportional relationship between fluoride concentration and dentinal lesion remineralization from 0.1 to 10.0 ppm. In the present study, the formation of a well-remineralized surface layer inhibited remineralization at the lesion front. On the other hand, the lesion front remineralization was found to be independent of fluoride concentration. Conclusion. Our results stated that for effective remineralization of dentinal lesions to the innermost part, fluoride levels from 1.0 to 5.0 ppm have the highest efficiency.